1995
DOI: 10.1007/bf01857872
|View full text |Cite
|
Sign up to set email alerts
|

Spouse Encouragement of self-reliance and other-reliance in rheumatoid arthritis couples

Abstract: Studying and helping couples burdened with a major life stressor such as rheumatoid arthritis (RA) can be enhanced by employing well-understood conceptual and empirical frameworks, in our research person/environment fit (P x E) models. We measured P x E effects in a sample of 62 rheumatoid arthritis (RA) patients with locus of control beliefs, age, and the health status of the subjects as the Person variables and their spouses' control encouragement as the Environment variable. As predicted, externals were mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…This result confirmed the Anxiety, Stress, & Coping 249 compensation hypothesis postulating that deficits in self-efficacy can be compensated by social support, which has been found in previous research on resource loss due to aging (Lachman et al, 1994;Warner et al, 2011) or diseases (Aymanns, 1992;Reich & Zautra, 1995). However, as opposed to previous studies that found higher social support to be detrimental to health outcomes if combined with higher self-efficacy (interference hypothesis; Warner et al, 2011), no such effect emerged in this sample of earthquake survivors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result confirmed the Anxiety, Stress, & Coping 249 compensation hypothesis postulating that deficits in self-efficacy can be compensated by social support, which has been found in previous research on resource loss due to aging (Lachman et al, 1994;Warner et al, 2011) or diseases (Aymanns, 1992;Reich & Zautra, 1995). However, as opposed to previous studies that found higher social support to be detrimental to health outcomes if combined with higher self-efficacy (interference hypothesis; Warner et al, 2011), no such effect emerged in this sample of earthquake survivors.…”
Section: Discussionsupporting
confidence: 91%
“…A study on older adults with multiple chronic conditions found that this specific sample was able to maintain its sense of autonomy despite lower levels of selfefficacy if they received higher social support (Warner et al, 2011). Accordingly, individuals reporting lower self-efficacy and higher support were found to adjust more easily to health problems such as cancer (Aymanns, 1992) or rheumatoid arthritis (Reich & Zautra, 1995). Hence, even though higher self-efficacy beliefs are generally associated with more adaptive coping, the social support system can help out if self-efficacy is depleted.…”
Section: Interplay Of Social Support and Self-efficacymentioning
confidence: 93%
“…Spousal encouragement and emotional support also predict better psychological adjustment and adaptation to the disease (Reich & Zautra, 1995).…”
Section: Marital Interaction and Health Outcomesmentioning
confidence: 99%
“…Much of the research that has examined psychosocial adjustment in the arthritis population has involved patients with longstanding disease (2–4, 10, 19–21, 23, 27–32). Few investigations have focused on psychosocial factors present during the first 5 years of diagnosis (1, 22, 25, 26).…”
Section: Introductionmentioning
confidence: 99%